2009
DOI: 10.1364/ol.34.000971
|View full text |Cite
|
Sign up to set email alerts
|

Radial polarization induced surface plasmon virtual probe for two-photon fluorescence microscopy

Abstract: Surface plasmons excited by a focused femtosecond radially polarized beam on a metal surface form a standing wave pattern with a sharp peak that can be used as a “virtual probe” for surface plasmon microscopy. The rotational symmetry of radially polarized light effectively provides the TM polarization required for coupling to the surface plasmons while the short pulse nature of the probe allows for nonlinear processes to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 11 publications
0
42
0
1
Order By: Relevance
“…Moreover, there have been very few attempts to investigate a systematic design method for multi-focal MFZPs even though such a method could have a huge impact on improvements in laser micro-machining, optical trapping, chemical sensing, biomedical sensing, confocal collimation, achromatic optics, etc. [14][15][16][17][18][19][20][21]. Thus, we think that this field merits additional research.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there have been very few attempts to investigate a systematic design method for multi-focal MFZPs even though such a method could have a huge impact on improvements in laser micro-machining, optical trapping, chemical sensing, biomedical sensing, confocal collimation, achromatic optics, etc. [14][15][16][17][18][19][20][21]. Thus, we think that this field merits additional research.…”
Section: Introductionmentioning
confidence: 99%
“…Kano et al reported the first experimental result concerning an efficient excitation of local SPPs, by using the zeroth-order BB [15]. More recently, radially-polarized BBs have been demonstrated to provide the TM polarization required for the effective coupling to the SPPs, which can be used as a virtual probe for the two-photon fluorescence microscopy [16]. We point out that the evanescent BBs can be obtained irrespective of the transverse profile of the radially-polarized impinging beam [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Radially polarized light can play a very important role in many research fields, such as Raman spectroscopy [1], optical ray generation [2][3][4], nonlinear microscopy [5], and microfabrication [6], and also for THz applications [7,8]. Surface plasmon polaritons (SPPs) excited on a metallic conical structure can realize adiabatic compression when a radial mode, also known as TM 0 mode, is excited on the cone [9,10].…”
mentioning
confidence: 99%